FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES OF ATENOLOL - Budhathoki, Uttam; Gartoulla, Kshitij; Shakya, Shailendra (INDONESIAN JOURNAL OF PHARMACY, 2016)
This study was carried out to develop matrix based transdermal patches containing Atenolol. A 2 factors (HPMC (hydroxyl propyl methyl cellulose) K4M & PVP (Polyvinyl Pyrolidone) 3 level (23) factorial design was done using Design ExpertÂ® which gave 13 experiments. The patches were prepared by Solvent casting method. Propylene glycol (3%) and Tween 80 (6%) were used as plasticizer and permeation enhancer respectively. Physicochemical characteristics and In-Vitro permeation study of formulated transdermal patches were carried out. Contour plot suggested 770 mg of PVP and 265 mg of HPMC K4M in Optimized formulation.Â